Science play! : beginning discoveries for 2- to 6-year-olds - Hauser, Jill Frankel, 1950- (Williamson Little Hands book., 1998)
Contains sixty-five activities that introduce readers to scientific exploration, including such subjects as weather, soil science, plants, color, and light.